The effects of Glomus intraradices on seedling growth parameters of Sage (Salvia officinalis L.) under salinity stress conditions - Tunçtürk, R.; Tunçtürk, M.; Rezaee Danesh, Y.; Najafi, S.; Toprak, T. (International Journal of Agricultural Technology, 2024)
Salinity is a significant abiotic stress that adversely affects plant growth and development, threatening global agricultural productivity, particularly in arid and semi-arid regions. Results indicated that increasing salt concentrations significantly inhibited seedling growth in all studied parameters, with control plants (0 mM) exhibiting the highest growth values. The tallest plants measured 23.16 cm in the control treatment, while those exposed to 200 mM salt reached only 13.12 cm. Although AMF applications did not show significant effects on plant height, they positively influenced growth parameters in salt-free conditions. Statistical analysis revealed significant interactions between salt levels and AMF on root fresh and dry weights, with the highest values recorded in the control group. Furthermore, AMF applications generally promoted growth, particularly in non-saline conditions, corroborating findings from previous research highlighting mycorrhizae's role in enhancing plant stress tolerance. In conclusion, the research findings emphasize the detrimental impact of salinity on plant development and the potential of mycorrhizal inoculation as a strategy to mitigate these effects. These findings contribute to understanding the beneficial role of AMF in improving salt tolerance and promoting sustainable agricultural practices in saline-prone environments